Optimisation des conditions aux frontieres par algorithmes genetiques: Optimisation des conditions aux frontieres par algorithmes genetiques - Marcelin, Jean-Luc (European Journal of Computational Mechanics, 1995)
This work examines the possibility of using a stochastic method, called the genetic algorithm for optimization of boundary conditions in finite elements calculations. The examples show that using genetic algorithms in order to optimize boundary conditions is an efficielll way.